Exploring the Antioxidant Potential of Gellan and Guar Gums in Wound Healing - Gianina Dodi; Rosina E. Sabau; Bianca E.-B. Crețu; Ioannis Gardikiotis (MDPI AG, 2023)
It is acknowledged that the presence of antioxidants boosts the wound-healing process. Many biopolymers have been explored over the years for their antioxidant potential in wound healing, but limited research has been performed on gum structures and their derivatives. This review aims to evaluate whether the antioxidant properties of gellan and guar gums and wound healing co-exist. PubMed was the primary platform used to explore published reports on the antioxidant wound-healing interconnection, wound dressings based on gellan and guar gum, as well as the latest review papers on guar gum. The literature search disclosed that some wound-healing supports based on gellan gum hold considerable antioxidant properties, as evident from the results obtained using different antioxidant assays. It has emerged that the antioxidant properties of guar gum are overlooked in the wound-healing field, in most cases, even if this feature improves the healing outcome. This review paper is the first that examines guar gum vehicles throughout the wound-healing process. Further research is needed to design and evaluate customized wound dressings that can scavenge excess reactive oxygen species, especially in clinical practice.